Palladium Supported on Calcined Coconut Shell Fiber (Pd/CCSF) as an Efficient and Sustainable Catalyst: Microwave-Assisted Synthesis of C–S Cross-Coupling Derivatives in DMF - Katla, Ramesh; Katla, Rakhi; Kern, Gabriela; Rosa, Clarissa H.; Rosa, Gilber R. (Synthesis, 2025)
The palladium supported on calcined coconut shell fiber (Pd/CCSF) catalyst was synthesized using an eco-friendly agro-industrial material, CCSF, with PdCl₂ supported on it. This catalyst was used for the first time in the development of a C–S cross-coupling reaction between various benzene thiols and 4,7-dibromo-2,1,3-benzothiadiazole or 5-bromo-2,1,3-benzothiadiazole under microwave irradiation at 75 °C (200 W, 100 psi) in DMF, with K₂CO₃ as the base. The catalyst was characterized using scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS) analyses. Furthermore, it was recycled and reused for up to four catalytic cycles without any loss of efficiency. A proposed mechanistic pathway for the C–S cross-coupling reaction is also included in this article.
Keywords: Palladium; Coconut Shell Fiber (CCSF); Cross-coupling; Benzene thiols; MWI